Heat dissipation material and method for producing heat dissipation material

By using heat dissipative materials prepared by using phenolic resin and carbon-based materials, the problems of high cost and easy conductivity of metal materials are solved, and the combination of efficient heat dissipation and mechanical strength is achieved, and the stability and life of electronic equipment are improved.

CN119613916APending Publication Date: 2025-03-14GUANGDONG JUXINYUAN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411682298.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The metal materials used in existing electronic equipment are costly and easily conductive, making it difficult to ensure long-term stability while dissipating heat efficiently.

Method used

A heat dissipation material is used, which consists of phenolic resin, curing agent, carbon nanotubes, carbon fibers and graphene. By pretreating fillers and heating the stirred resin, a three-dimensional network structure and thermal conductivity network are formed to improve the thermal conductivity and mechanical properties of the material.

Benefits of technology

It achieves efficient heat conduction and mechanical strength, reduces material costs, and improves the heat dissipation performance and service life of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613916A_ABST
    Figure CN119613916A_ABST
Patent Text Reader

Abstract

The invention relates to a heat dissipation material and a preparation method thereof, and belongs to the field of heat dissipation materials. The heat dissipation material comprises the following components: phenolic resin; a curing agent; a carbon nanotube; carbon fibers; and graphene. According to the heat dissipation material, the phenolic resin is used as a base material, and the heat dissipation material has good heat resistance, chemical stability and mechanical performance. In the heat dissipation material, mechanical support is provided, a three-dimensional network structure is formed through reaction with the curing agent, the heat conduction filler is wrapped in the three-dimensional network structure, and the overall structural stability is achieved. And the curing agent is used for carrying out cross-linking reaction with the phenolic resin. Carbon atoms in the carbon nanotubes form a highly ordered covalent bond structure through sp2 hybridization, and electrons can efficiently transmit heat in the carbon nanotubes. The excellent mechanical performance of the carbon fiber can provide good support and strength for the heat dissipation material, and the material is prevented from being broken or deformed in the using process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heat dissipation materials, in particular to a heat dissipation material and a preparation method of the heat dissipation material. Background Art

[0002] Nowadays, electronic devices are striding towards high power and high performance. This development trend has certainly brought more powerful functions and a more excellent experience, but at the same time, it cannot be ignored that its heat generation has also increased significantly. If the heat cannot be dissipated in a timely and efficient manner, it will accumulate rapidly and continue to grow. In this way, the components inside the electronic equipment will face severe tests and may not be able to maintain normal working conditions. The level of heat dissipation performance has become one of the key factors determining the service life of electronic equipment, and plays a vital role in the stable operation and long-term reliability of the entire electronic equipment. Metal materials are often used in the field of heat dissipation materials, but metal materials are more expensive and of higher quality. At the same time, due to their use inside electronic equipment, metal materials are easy to conduct electricity and are more susceptible to environmental influences after long-term use, which may affect their use. Summary of the invention

[0003] Based on this, it is necessary to provide a heat dissipation material to address the problems of high cost and high quality of metal materials.

[0004] A heat dissipation material comprises the following components:

[0005] Phenolic resin;

[0006] Curing agent;

[0007] Carbon nanotubes;

[0008] Carbon fiber;

[0009] Graphene.

[0010] The above-mentioned heat dissipation material uses phenolic resin as the matrix material, which has good heat resistance, chemical stability and mechanical properties. The benzene ring and phenolic hydroxyl group in its molecular structure give it high rigidity and thermal stability. In the heat dissipation material, it not only provides mechanical support, but also forms a three-dimensional network structure by reacting with the curing agent, wrapping the thermal conductive filler in it to achieve overall structural stability. The role of the curing agent is to cross-link with the phenolic resin, so that the resin changes from a linear structure to a three-dimensional network structure, thereby improving the hardness, strength and heat resistance of the material. The carbon atoms in the carbon nanotubes are sp 2Hybridization forms a highly ordered covalent bond structure in which electrons can efficiently transfer heat. Carbon nanotubes can interweave in the material to form a heat-conducting network, greatly improving the efficiency of heat conduction in the material. The excellent mechanical properties of carbon fiber can provide good support and strength for heat dissipation materials, preventing the material from breaking or deforming during use. In the microstructure of carbon fiber, there are graphite crystallites arranged along the fiber axis, and these microcrystalline structures are conducive to heat conduction. The large specific surface area of ​​graphene is conducive to interface contact with other materials, enhancing the efficiency of interface heat conduction.

[0011] In one embodiment, the heat dissipation material, by weight, has the following components:

[0012] 40-50 parts of phenolic resin;

[0013] 9-10 parts of curing agent;

[0014] 3-5 parts of carbon nanotubes;

[0015] Carbon fiber 33-37 parts;

[0016] 2-4 parts of graphene.

[0017] In one embodiment, the curing agent is one of hexamethylenetetramine, m-phenylenediamine, diethylenetriamine, p-toluenesulfonic acid, and phenolsulfonic acid.

[0018] In one embodiment, the length of the carbon fiber is 3-5 mm.

[0019] The second aspect of the present application discloses a method for preparing a heat dissipation material, comprising the following steps:

[0020] S1. pretreating carbon nanotubes, carbon fibers and graphene to form fillers;

[0021] S2. The phenolic resin matrix is ​​heated and stirred, and the filler formed by the pretreatment is added to the phenolic resin during the stirring process;

[0022] S3. The curing agent is slowly added to the mixed resin and filler system while stirring;

[0023] S4. Input the evenly mixed material into the prepared mold, and put the mold containing the material into an oven for curing.

[0024] The preparation method of the above-mentioned heat dissipation material, the pretreatment of carbon nanotubes, carbon fibers and graphene can improve their surface properties by chemical or physical methods, so that their hydrophilicity or hydrophobicity is more suitable for compatibility with phenolic resin. In this way, the interfacial contact area between the filler and the resin can be increased, and the thermal conductivity and mechanical properties of the material can be significantly improved. In addition, the pretreatment helps to disperse the filler and avoid aggregation in the resin, thereby improving the effective utilization rate of the filler in the matrix and enhancing the heat dissipation performance. Heating the phenolic resin can reduce its viscosity, improve fluidity, and enable the filler to be more evenly mixed into the resin to form a more homogeneous composite material. During the stirring process, the addition of the filler allows it to fully contact with the resin, which helps to wet the filler, thereby improving the physical and thermal properties of the composite material. Slowly adding a curing agent and continuously stirring can reduce the generation of bubbles, ensure the uniformity of the resin system, reduce defects, and improve the density and strength of the material. By controlling the addition rate of the curing agent, the speed of the curing reaction can be adjusted to avoid the internal stress of the material caused by the violent reaction, thereby improving the mechanical properties and stability of the final product. Pouring the mixed material into the mold ensures that the material maintains the predetermined shape during the curing process, improving the consistency and repeatability of the product. Curing in an oven provides a uniform temperature environment, which helps the material to cross-link evenly, improve its thermal conductivity and compressive strength, and ensure stable heat dissipation performance.

[0025] In one embodiment, in step S1, the specific steps of pre-treating the carbon nanotubes, carbon fibers and graphene are as follows:

[0026] S11. The mass fraction of 3-5 carbon nanotubes is added to the dispersant solution, the mass ratio of carbon nanotubes to the dispersant solution is 1:0.5-1:1;

[0027] S12. Add deionized water to prepare a dispersion having a mass fraction of carbon nanotubes of 1% to 3%;

[0028] S13. Ultrasonic treatment of the dispersion was performed using an ultrasonic cell crusher to obtain a carbon nanotube filler;

[0029] S14. Cut the carbon fiber into 3-5 mm lengths;

[0030] S15. The cut carbon fiber is placed in concentrated nitric acid for surface oxidation treatment;

[0031] S16. The treated carbon fiber is rinsed with deionized water until neutral, and then dried in a vacuum drying oven at 80-100 ° C for 6-8 hours to obtain a carbon fiber filler;

[0032] S17. Adding 2-4 parts by mass of graphene to N-methylpyrrolidone, stirring at a stirring speed of 1000-1500 r / min for 30-60 minutes, the graphene is initially dispersed in N-methylpyrrolidone to obtain a preliminary graphene solution;

[0033] S18. Then, the graphene preliminary solution is subjected to ultrasonic treatment with an ultrasonic power of 200-300 W and an ultrasonic time of 30-60 minutes to further improve the dispersion uniformity of the graphene and obtain a graphene filler.

[0034] During the ultrasonic process, the dispersion will produce a cavitation effect. The microjets and shock waves generated by the rupture of the cavitation bubbles can effectively break up the agglomerates of carbon nanotubes and make them evenly dispersed in the solution. This dispersion treatment can enable the carbon nanotubes to better form a heat-conducting network when they are subsequently mixed with other materials, thereby improving the efficiency of heat conduction. The carbon fibers are cut into 3-5mm lengths to increase their dispersibility in the material and their binding force with the matrix. Nitric acid treatment can introduce oxygen-containing functional groups, such as carboxyl and hydroxyl groups, on the surface of the carbon fibers, which can improve the compatibility and interfacial bonding between the carbon fibers and the phenolic resin. The enhanced interfacial bonding force can reduce the scattering of heat at the interface and improve the efficiency of heat transfer from the carbon fibers to the resin matrix, thereby improving the overall heat dissipation performance. N-methylpyrrolidone is a good organic solvent with good solubility and dispersibility for graphene. From a molecular level, the molecular structure of N-methylpyrrolidone can interact with the surface of graphene, reduce the van der Waals force between graphene sheets, and make it better dispersed in the solution. This evenly dispersed graphene can more effectively increase the heat conduction path in the heat dissipation material and improve the overall thermal conductivity of the material.

[0035] In one embodiment, the dispersant is sodium dodecylbenzene sulfonate.

[0036] In one embodiment, the ultrasonic power of the ultrasonic treatment is set to 300-500W, and the ultrasonic time is 1-2 hours;

[0037] In one of the embodiments, the mass ratio of the concentrated nitric acid to the carbon fiber is 5:1-10:1, the treatment time is 2-4 hours, and the temperature is controlled at 60-80°C.

[0038] In one embodiment, in step S2, the phenolic resin matrix is ​​heated and stirred, and the specific steps of adding the filler formed by the pretreatment into the phenolic resin during the stirring process are as follows:

[0039] S21. The mass fraction of 40-50 phenolic resin is heated to 60-80 ° C, and the heating process is continuously stirred;

[0040] S22. The pretreated carbon nanotube dispersion, carbon fiber and graphene dispersion are slowly added to the heated phenolic resin in sequence while stirring with a mechanical stirrer;

[0041] S23. The stirring speed is 500-800 r / min and the stirring time is 40-60 minutes to evenly distribute the filler in the phenolic resin matrix.

[0042] Heating the phenolic resin reduces its viscosity and increases its fluidity. During the heating process, stir continuously to ensure that the resin is heated evenly. The temperature can be better controlled by heating in a constant temperature water bath or oil bath to avoid local overheating that causes the resin to deteriorate in performance. From the perspective of molecular dynamics, increasing the temperature can increase the thermal motion energy of the phenolic resin molecules, making their molecular chains more stretched, which is conducive to subsequent mixing and reaction with fillers. Carbon nanotubes, with their high aspect ratio, construct a thermally conductive network skeleton in the resin matrix, providing an axial channel for rapid heat conduction. Carbon fibers play a role in strengthening and conducting heat on a larger scale, and cooperate with carbon nanotubes to construct multi-level thermal conduction channels. The two-dimensional sheet structure of graphene can be filled in the gaps between carbon nanotubes and carbon fibers, further increasing the density of the heat conduction path, achieving efficient heat transfer in different dimensions from a microscopic perspective, and improving the overall thermal conductivity of the material.

[0043] In one embodiment, in step S4, the specific steps of placing the mold containing the material into an oven for curing are as follows:

[0044] Perform low-temperature pre-curing, set the curing temperature to 80-100°C and the time to 1-2 hours;

[0045] Perform medium temperature curing, set the temperature to 120-140℃, and last for 2-3 hours;

[0046] Perform high temperature curing, set the temperature to 160-180℃, and the time is 1-2 hours.

[0047] In the low-temperature pre-curing stage, the curing agent further reacts with the phenolic resin to form a preliminary cross-linking structure, which gives the material a certain strength and shape stability and reduces the internal stress generated by subsequent high-temperature curing. From a thermodynamic point of view, the reaction rate is relatively slow at low temperatures, which can make the cross-linking reaction proceed smoothly and avoid the internal stress concentration caused by too fast reaction. At the same time, the initially formed cross-linking structure can provide a certain strength for the material to prevent deformation during subsequent processing. In the medium-temperature curing stage, the cross-linking reaction is accelerated, and the resin matrix gradually forms a three-dimensional network structure, and the hardness, strength and heat resistance of the material are further improved. In this temperature range, the activity of the curing agent increases, the reaction rate with the phenolic resin is accelerated, and more cross-linking points are formed, making the structure of the material more compact and the performance significantly improved. In the high-temperature post-curing stage, the curing reaction is more complete, the unreacted groups are eliminated, and the performance stability and durability of the material are improved. High temperature can activate the remaining unreacted groups and make them participate in the cross-linking reaction, thereby making the cross-linking structure of the material more perfect. From the perspective of the microstructure of the material, the perfect cross-linking structure can improve the thermal stability and mechanical properties of the material and reduce the performance degradation caused by factors such as thermal expansion and contraction during use. During the entire curing process, the temperature in the oven should be kept uniform, which can be achieved by using circulating air or a heat plate to ensure uniform material properties. Uneven temperature may lead to different degrees of curing in different parts of the material, thus affecting the overall performance of the material, resulting in problems such as low local strength and large differences in thermal conductivity.

[0048] In one embodiment, in step S3, the curing agent is slowly added to the mixed resin and filler system while stirring as follows:

[0049] S31. Set the required curing agent mass M g and the total mass of phenolic resin and filler M t ;

[0050] S32. Introduce a machine learning model to predict the optimal curing agent addition rate R based on historical data pred , where R pred The expression is as follows:

[0051] R pred =f(M t , T initial , η initial , C)

[0052] Among them, R pred is the predicted curing agent addition rate, M t is the total mass, T initial is the initial temperature, η initial is the initial viscosity, C is the mass of the curing agent, and the function f uses multiple inputs to train the model;

[0053] S33. Set the target mixture temperature T target and target viscosity η target , and calculate the corresponding curing agent addition rate:

[0054]

[0055] Wherein, Mg is the total mass of the curing agent, and T is the set addition time;

[0056] S34. Dynamically adjust the curing agent addition rate, wherein the addition rate is expressed as follows:

[0057] R adjusted =R pred +k f ·(T target -T m )+k v ·(η target -η(t)

[0058] Among them, R adjusted is the adjusted rate, K f is the adjustment coefficient of the temperature feedback effect, K v is the adjustment factor for the feedback effect of viscosity, Tm is the current temperature of the mixture, and η(t) is the change in the viscosity of the mixture with time;

[0059] S35. Set stirring speed V s , dynamically adjusted according to real-time viscosity and temperature changes:

[0060]

[0061] Among them, V s is the stirring speed, V mix is the volume of the mixture, k is the proportionality constant, k s is the adjustment factor related to temperature change, K v is the adjustment factor related to the viscosity change;

[0062] S36. Use optimization algorithms to adjust flow and stirring speed to achieve multivariable optimization:

[0063]

[0064] Among them, J is the objective function, Xi represents different control parameters, Xtarget represents the target value corresponding to the control parameter, ω i is the weight;

[0065] S37. When the preset total mass of curing agent M is reached gWhen the curing agent is added, the stirring speed is set at 800-1200r / min and the stirring is maintained for 10 minutes to ensure uniform mixing;

[0066] S38. Strictly control the system temperature through the heating device and maintain it at 25-30℃ to avoid premature reaction of the curing agent due to temperature fluctuations.

[0067] By introducing machine learning models and historical data, the optimal curing agent addition rate R can be accurately predicted. pred This optimization reduces the uncertainty of curing agent addition and ensures that the mixture can achieve the best performance during the curing process. m and viscosity η(t), dynamically adjust the curing agent addition rate R adjusted This real-time feedback mechanism ensures uniform distribution of the curing agent, avoiding uneven reactions caused by temperature or viscosity fluctuations, thereby improving the consistency and reliability of the final material. By setting the dynamic stirring speed V related to temperature and viscosity s , the stirring speed can be flexibly adjusted when the viscosity of the mixture changes. This adaptive stirring ensures the uniformity of the material, enhances the interaction between the curing agent and the resin and filler, and improves the overall performance of the material. By adjusting the flow rate and stirring speed using an optimization algorithm, the best combination of control parameters can be found under different operating conditions. This multivariable optimization improves the stability and efficiency of the process, thereby reducing production time and material waste. When the preset total mass of curing agent M is reached g When the curing agent is added, the addition of curing agent is automatically stopped to ensure the accuracy of the amount added. This precise control helps to achieve the expected material properties and reduce the risk of defects caused by excessive or insufficient curing agent. The system temperature is strictly controlled at 25-30°C by the heating device to avoid premature reaction of the curing agent caused by temperature fluctuations and ensure the controllability of the curing process. This stable temperature environment helps to improve the curing efficiency and ensure that the mechanical and chemical properties of the final material meet the design requirements. The combination of the above measures ensures the uniformity of the mixture during the curing process, the controllability of the reaction, and the stability of the material properties, thereby improving the overall properties of the final prepared material, such as thermal conductivity, mechanical strength and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 A flow chart of a method for preparing a heat dissipation material;

[0069] Figure 2 A flow chart of specific steps for pre-treating carbon nanotubes, carbon fibers and graphene;

[0070] Figure 3 A flowchart of the specific steps for heating and stirring the phenolic resin matrix and adding the pre-treated filler into the phenolic resin during the stirring process. DETAILED DESCRIPTION

[0071] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0072] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0073] The heat dissipation material and the method for preparing the heat dissipation material according to some embodiments of the present invention will be described below with reference to the accompanying drawings.

[0074] Example 1

[0075] This embodiment provides a heat dissipation material, the components of which are as follows by weight: 40 parts of phenolic resin, 9 parts of curing agent, 3 parts of carbon nanotubes, 33 parts of carbon fibers, and 2 parts of graphene.

[0076] The preparation method of the heat dissipation material is as follows:

[0077] Weigh 3 parts of carbon nanotubes, 33 parts of carbon fibers and 2 parts of graphene for pretreatment to form a filler;

[0078] Weigh 40 parts of phenolic resin, heat and stir the phenolic resin matrix, and add the filler formed by pretreatment into the phenolic resin during the stirring process;

[0079] Weigh 9 parts of curing agent and slowly add the curing agent to the mixed resin and filler system while stirring;

[0080] The evenly mixed material is input into the prepared mold, and the mold containing the material is placed in an oven for curing.

[0081] Example 2

[0082] This embodiment provides a heat dissipation material, the components of which are as follows in parts by weight: 42 parts phenolic resin, 9.5 parts curing agent, 3.5 parts carbon nanotubes, 34 parts carbon fibers, and 2.5 parts graphene.

[0083] The preparation method of the heat dissipation material is as follows:

[0084] Weigh 3.5 parts of carbon nanotubes, 34 parts of carbon fibers and 2.5 parts of graphene for pretreatment to form a filler;

[0085] Weigh 42 parts of phenolic resin, heat and stir the phenolic resin matrix, and add the filler formed by pretreatment into the phenolic resin during the stirring process;

[0086] Weigh 9.5 parts of curing agent and slowly add the curing agent to the mixed resin and filler system while stirring;

[0087] The evenly mixed material is input into the prepared mold, and the mold containing the material is placed in an oven for curing.

[0088] Example 3

[0089] This embodiment provides a heat dissipation material, the components of which are as follows in parts by weight: 45 parts of phenolic resin, 9.8 parts of curing agent, 4 parts of carbon nanotubes, 35 parts of carbon fiber, and 3 parts of graphene.

[0090] The preparation method of the heat dissipation material is as follows:

[0091] Weigh 4 parts of carbon nanotubes, 35 parts of carbon fibers and 3 parts of graphene for pretreatment to form a filler;

[0092] Weigh 45 parts of phenolic resin, heat and stir the phenolic resin matrix, and add the filler formed by pretreatment into the phenolic resin during the stirring process;

[0093] Weigh 9.8 parts of curing agent and slowly add the curing agent to the mixed resin and filler system while stirring;

[0094] The evenly mixed material is input into the prepared mold, and the mold containing the material is placed in an oven for curing.

[0095] Example 4

[0096] This embodiment provides a heat dissipation material, the components of which are as follows in parts by weight: phenolic resin 48, curing agent 10, carbon nanotubes 4.5, carbon fibers 36, and graphene 3.5.

[0097] The preparation method of the heat dissipation material is as follows:

[0098] Weigh 4.5 parts of carbon nanotubes, 36 parts of carbon fibers and 3.5 parts of graphene for pretreatment to form a filler;

[0099] Weigh 48 parts of phenolic resin, heat and stir the phenolic resin matrix, and add the filler formed by pretreatment into the phenolic resin during the stirring process;

[0100] Weigh 10 parts of curing agent and slowly add the curing agent to the mixed resin and filler system while stirring;

[0101] The evenly mixed material is input into the prepared mold, and the mold containing the material is placed in an oven for curing.

[0102] Example 5

[0103] This embodiment provides a heat dissipation material, the components of which are as follows by weight: phenolic resin 50, curing agent 10, carbon nanotubes 5, carbon fibers 37, and graphene 4.

[0104] The preparation method of the heat dissipation material is as follows:

[0105] Weigh 5 parts of carbon nanotubes, 37 parts of carbon fibers and 4 parts of graphene for pretreatment to form a filler;

[0106] Weigh 50 parts of phenolic resin, heat and stir the phenolic resin matrix, and add the filler formed by pretreatment into the phenolic resin during the stirring process;

[0107] Weigh 10 parts of curing agent and slowly add the curing agent to the mixed resin and filler system while stirring;

[0108] The evenly mixed material is input into the prepared mold, and the mold containing the material is placed in an oven for curing.

[0109] Product Testing

[0110] The heat dissipation materials of Examples 1, 2, 3, 4 and 5 were compared with aluminum, and the results are shown in Table 1:

[0111] Table 1 Thermal resistance table

[0112] Example 1 Example 2 Example 3 Example 4 Example 5 aluminum 0.5℃ / W 0.4℃ / W 0.3℃ / W 0.2℃ / W 0.2℃ / W 0.15℃ / W

[0113] Through testing, it can be seen that the thermal resistance of Examples 4 and 5 is relatively close to the thermal resistance of aluminum. In addition, due to material issues, aluminum as a heat dissipation material needs to consider issues such as material thickness, material strength, processing difficulty, heat dissipation area and cost.

[0114] In summary, the heat dissipation materials prepared by Example 4 and Example 5 have better comprehensive performance.

[0115] Example 6

[0116] like Figure 1 As shown, a method for preparing a heat dissipation material comprises the following steps:

[0117] S1. pretreating carbon nanotubes, carbon fibers and graphene to form fillers;

[0118] S2. The phenolic resin matrix is ​​heated and stirred, and the filler formed by the pretreatment is added to the phenolic resin during the stirring process;

[0119] S3. The curing agent is slowly added to the mixed resin and filler system while stirring;

[0120] S4. Input the evenly mixed material into the prepared mold, and put the mold containing the material into an oven for curing.

[0121] Pretreatment of carbon nanotubes, carbon fibers and graphene can improve their surface properties by chemical or physical methods, making their hydrophilicity or hydrophobicity more suitable for compatibility with phenolic resin. This can increase the interfacial contact area between the filler and the resin, significantly improving the thermal conductivity and mechanical properties of the material. In addition, pretreatment helps to disperse the filler and avoid aggregation in the resin, thereby improving the effective utilization of the filler in the matrix and enhancing the heat dissipation performance. Heating the phenolic resin can reduce its viscosity and improve its fluidity, so that the filler can be mixed more evenly into the resin to form a more homogeneous composite material. During the stirring process, the addition of the filler allows it to fully contact with the resin, which helps to wet the filler, thereby improving the physical and thermal properties of the composite material. Slowly adding the curing agent and continuously stirring can reduce the generation of bubbles, ensure the uniformity of the resin system, reduce defects, and increase the density and strength of the material. By controlling the addition rate of the curing agent, the speed of the curing reaction can be adjusted to avoid the internal stress of the material caused by the violent reaction, thereby improving the mechanical properties and stability of the final product. Pouring the mixed material into the mold can ensure that the material maintains the predetermined shape during the curing process and improve the consistency and repeatability of the product. When curing in an oven, a uniform temperature environment can be provided, which helps the uniform cross-linking of the material, improves its thermal conductivity and compressive strength, and ensures stable heat dissipation performance.

[0122] In addition to the features of the above embodiments, this embodiment further defines that: the curing agent is one of hexamethylenetetramine, m-phenylenediamine, diethylenetriamine, p-toluenesulfonic acid, and phenolsulfonic acid.

[0123] In addition to the features of the above embodiment, this embodiment further defines that the length of the carbon fiber is 3-5 mm, wherein the length of the carbon fiber can be 3 mm, 4 mm and 5 mm.

[0124] like Figure 2 As shown, in addition to the features of the above embodiment, this embodiment further defines: in step S1, the specific steps of pre-treating the carbon nanotubes, carbon fibers and graphene are as follows:

[0125] S11. The mass fraction of 3-5 carbon nanotubes is added to the dispersant solution, the mass ratio of carbon nanotubes to the dispersant solution is 1:0.5-1:1;

[0126] S12. Add deionized water to prepare a dispersion having a mass fraction of carbon nanotubes of 1% to 3%;

[0127] S13. Ultrasonic treatment of the dispersion was performed using an ultrasonic cell crusher to obtain a carbon nanotube filler;

[0128] S14. Cut the carbon fiber into 3-5 mm lengths;

[0129] S15. The cut carbon fiber is placed in concentrated nitric acid for surface oxidation treatment;

[0130] S16. The treated carbon fiber is rinsed with deionized water until neutral, and then dried in a vacuum drying oven at 80-100 ° C for 6-8 hours to obtain a carbon fiber filler;

[0131] S17. Adding 2-4 parts by mass of graphene to N-methylpyrrolidone, stirring at a stirring speed of 1000-1500 r / min for 30-60 minutes, the graphene is initially dispersed in N-methylpyrrolidone to obtain a preliminary graphene solution;

[0132] S18. Then, the graphene preliminary solution is subjected to ultrasonic treatment with an ultrasonic power of 200-300 W and an ultrasonic time of 30-60 minutes to further improve the dispersion uniformity of the graphene and obtain a graphene filler.

[0133] During the ultrasonic process, the dispersion will produce a cavitation effect. The microjets and shock waves generated by the rupture of the cavitation bubbles can effectively break up the agglomerates of carbon nanotubes and make them evenly dispersed in the solution. This dispersion treatment can enable the carbon nanotubes to better form a heat-conducting network when they are subsequently mixed with other materials, thereby improving the efficiency of heat conduction. The carbon fibers are cut into 3-5mm lengths to increase their dispersibility in the material and their binding force with the matrix. Nitric acid treatment can introduce oxygen-containing functional groups, such as carboxyl and hydroxyl groups, on the surface of the carbon fibers, which can improve the compatibility and interfacial bonding between the carbon fibers and the phenolic resin. The enhanced interfacial bonding force can reduce the scattering of heat at the interface and improve the efficiency of heat transfer from the carbon fibers to the resin matrix, thereby improving the overall heat dissipation performance. N-methylpyrrolidone is a good organic solvent with good solubility and dispersibility for graphene. From a molecular level, the molecular structure of N-methylpyrrolidone can interact with the surface of graphene, reduce the van der Waals force between graphene sheets, and make it better dispersed in the solution. This evenly dispersed graphene can more effectively increase the heat conduction path in the heat dissipation material and improve the overall thermal conductivity of the material.

[0134] In addition to the features of the above embodiments, this embodiment further defines that: the dispersant is sodium dodecylbenzene sulfonate.

[0135] In addition to the features of the above embodiments, this embodiment further defines that: the ultrasonic power of the ultrasonic treatment is set to 300-500W, and the ultrasonic time is 1-2 hours.

[0136] In addition to the features of the above embodiments, this embodiment further defines that: the mass ratio of the concentrated nitric acid to the carbon fiber is 5:1-10:1, the treatment time is 2-4 hours, and the temperature is controlled at 60-80°C.

[0137] like Figure 3 As shown, in addition to the features of the above embodiment, this embodiment further defines: in step S2, the phenolic resin matrix is ​​heated and stirred, and the specific steps of adding the filler formed by the pretreatment into the phenolic resin during the stirring process are as follows:

[0138] S21. The mass fraction of 40-50 phenolic resin is heated to 60-80 ° C, and the heating process is continuously stirred;

[0139] S22. The pretreated carbon nanotube dispersion, carbon fiber and graphene dispersion are slowly added to the heated phenolic resin in sequence while stirring with a mechanical stirrer;

[0140] S23. The stirring speed is 500-800 r / min and the stirring time is 40-60 minutes to evenly distribute the filler in the phenolic resin matrix.

[0141] Heating the phenolic resin reduces its viscosity and increases its fluidity. During the heating process, stir continuously to ensure that the resin is heated evenly. The temperature can be better controlled by heating in a constant temperature water bath or oil bath to avoid local overheating that causes the resin to deteriorate in performance. From the perspective of molecular dynamics, increasing the temperature can increase the thermal motion energy of the phenolic resin molecules, making their molecular chains more stretched, which is conducive to subsequent mixing and reaction with fillers. Carbon nanotubes, with their high aspect ratio, construct a thermally conductive network skeleton in the resin matrix, providing an axial channel for rapid heat conduction. Carbon fibers play a role in strengthening and conducting heat on a larger scale, and cooperate with carbon nanotubes to construct multi-level thermal conduction channels. The two-dimensional sheet structure of graphene can be filled in the gaps between carbon nanotubes and carbon fibers, further increasing the density of the heat conduction path, achieving efficient heat transfer in different dimensions from a microscopic perspective, and improving the overall thermal conductivity of the material.

[0142] In addition to the features of the above embodiment, this embodiment further defines that in step S4, the specific steps of placing the mold containing the material into an oven for curing are as follows:

[0143] Perform low-temperature pre-curing, set the curing temperature to 80-100°C and the time to 1-2 hours;

[0144] Perform medium temperature curing, set the temperature to 120-140℃, and last for 2-3 hours;

[0145] Perform high temperature curing, set the temperature to 160-180℃, and the time is 1-2 hours.

[0146] In the low-temperature pre-curing stage, the curing agent further reacts with the phenolic resin to form a preliminary cross-linking structure, which gives the material a certain strength and shape stability and reduces the internal stress generated by subsequent high-temperature curing. From a thermodynamic point of view, the reaction rate is relatively slow at low temperatures, which can make the cross-linking reaction proceed smoothly and avoid the internal stress concentration caused by too fast reaction. At the same time, the initially formed cross-linking structure can provide a certain strength for the material to prevent deformation during subsequent processing. In the medium-temperature curing stage, the cross-linking reaction is accelerated, and the resin matrix gradually forms a three-dimensional network structure, and the hardness, strength and heat resistance of the material are further improved. In this temperature range, the activity of the curing agent increases, the reaction rate with the phenolic resin is accelerated, and more cross-linking points are formed, making the structure of the material more compact and the performance significantly improved. In the high-temperature post-curing stage, the curing reaction is more complete, the unreacted groups are eliminated, and the performance stability and durability of the material are improved. High temperature can activate the remaining unreacted groups and make them participate in the cross-linking reaction, thereby making the cross-linking structure of the material more perfect. From the perspective of the microstructure of the material, the perfect cross-linking structure can improve the thermal stability and mechanical properties of the material and reduce the performance degradation caused by factors such as thermal expansion and contraction during use. During the entire curing process, the temperature in the oven should be kept uniform, which can be achieved by using circulating air or a heat plate to ensure uniform material properties. Uneven temperature may lead to different degrees of curing in different parts of the material, thus affecting the overall performance of the material, resulting in problems such as low local strength and large differences in thermal conductivity.

[0147] In addition to the features of the above embodiment, this embodiment further defines that in step S3, the specific steps of slowly adding the curing agent to the above mixed resin and filler system while stirring are as follows:

[0148] S31. Set the required curing agent mass M g and the total mass of phenolic resin and filler M t ;

[0149] S32. Introduce a machine learning model to predict the optimal curing agent addition rate R based on historical data pred , where R pred The expression is as follows:

[0150] R pred =f(M t , T initial , η initial , C)

[0151] Among them, Rpred is the predicted curing agent addition rate, M t is the total mass, T initial is the initial temperature, η initial is the initial viscosity, C is the mass of the curing agent, and the function f uses multiple inputs to train the model;

[0152] S33. Set the target mixture temperature T target and target viscosity η target , and calculate the corresponding curing agent addition rate:

[0153]

[0154] Wherein, Mg is the total mass of the curing agent, and T is the set addition time;

[0155] S34. Dynamically adjust the curing agent addition rate, wherein the addition rate is expressed as follows:

[0156] R adjusted =R pred +k f ·(T target -T m )+k v ·(η target -η(t)

[0157] Among them, R adjusted is the adjusted rate, K f is the adjustment coefficient of the temperature feedback effect, K v is the adjustment factor for the feedback effect of viscosity, Tm is the current temperature of the mixture, and η(t) is the change in the viscosity of the mixture with time;

[0158] S35. Set stirring speed V s , dynamically adjusted according to real-time viscosity and temperature changes:

[0159]

[0160] Among them, V s is the stirring speed, V mix is the volume of the mixture, k is the proportionality constant, k s is the adjustment factor related to temperature change, K v is the adjustment factor related to the viscosity change;

[0161] S36. Use optimization algorithms to adjust flow and stirring speed to achieve multivariable optimization:

[0162]

[0163] Among them, J is the objective function, Xi represents different control parameters, Xtarget represents the target value corresponding to the control parameter, ω i is the weight;

[0164] S37. When the preset total mass of curing agent M is reached g When the curing agent is added, the stirring speed is set at 800-1200r / min and the stirring is maintained for 10 minutes to ensure uniform mixing;

[0165] S38. Strictly control the system temperature through the heating device and maintain it at 25-30℃ to avoid premature reaction of the curing agent due to temperature fluctuations.

[0166] By introducing machine learning models and historical data, the optimal curing agent addition rate R can be accurately predicted. pred This optimization reduces the uncertainty of curing agent addition and ensures that the mixture can achieve the best performance during the curing process. m and viscosity η(t), dynamically adjust the curing agent addition rate R adjusted This real-time feedback mechanism ensures uniform distribution of the curing agent, avoiding uneven reactions caused by temperature or viscosity fluctuations, thereby improving the consistency and reliability of the final material. By setting the dynamic stirring speed V related to temperature and viscosity s , the stirring speed can be flexibly adjusted when the viscosity of the mixture changes. This adaptive stirring ensures the uniformity of the material, enhances the interaction between the curing agent and the resin and filler, and improves the overall performance of the material. By adjusting the flow rate and stirring speed using an optimization algorithm, the best combination of control parameters can be found under different operating conditions. This multivariable optimization improves the stability and efficiency of the process, thereby reducing production time and material waste. When the preset total mass of curing agent M is reached g When the curing agent is added, the addition of curing agent is automatically stopped to ensure the accuracy of the amount added. This precise control helps to achieve the expected material properties and reduce the risk of defects caused by excessive or insufficient curing agent. The system temperature is strictly controlled at 25-30°C by the heating device to avoid premature reaction of the curing agent caused by temperature fluctuations and ensure the controllability of the curing process. This stable temperature environment helps to improve the curing efficiency and ensure that the mechanical and chemical properties of the final material meet the design requirements. The combination of the above measures ensures the uniformity of the mixture during the curing process, the controllability of the reaction, and the stability of the material properties, thereby improving the overall properties of the final prepared material, such as thermal conductivity, mechanical strength and durability.

[0167] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0168] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A heat dissipation material, characterized in that: The components include: Phenolic resin; Curing agent; Carbon nanotubes; Carbon fiber; Graphene.

2. The heat dissipation material according to claim 1, characterized in that In terms of mass fractions, the mass fractions of the components are as follows: 40-50 parts of phenolic resin; 9-10 parts of curing agent; 3-5 parts of carbon nanotubes; Carbon fiber 33-37 parts; 2-4 parts of graphene. 3 . The heat dissipation material according to claim 2 , wherein the curing agent is one of hexamethylenetetramine, m-phenylenediamine, diethylenetriamine, p-toluenesulfonic acid and phenolsulfonic acid.

4. The heat dissipation material according to claim 2, characterized in that: The length of the carbon fiber is 3-5 mm.

5. A method for preparing a heat dissipation material, characterized in that: The steps include: S1. pretreating carbon nanotubes, carbon fibers and graphene to form fillers; S2. The phenolic resin matrix is ​​heated and stirred, and the filler formed by the pretreatment is added to the phenolic resin during the stirring process; S3. The curing agent is slowly added to the mixed resin and filler system while stirring; S4. Input the evenly mixed material into the prepared mold, and put the mold containing the material into an oven for curing.

6. The method for preparing a heat dissipation material according to claim 5, characterized in that: In step S1, the specific steps of pre-treating the carbon nanotubes, carbon fibers and graphene are as follows: S11. The mass fraction of 3-5 carbon nanotubes is added to the dispersant solution, the mass ratio of carbon nanotubes to the dispersant solution is 1:0.5-1:1; S12. Add deionized water to prepare a dispersion having a mass fraction of carbon nanotubes of 1% to 3%; S13. Ultrasonic treatment of the dispersion using an ultrasonic cell crusher to obtain a carbon nanotube filler; S14. Cut the carbon fiber into 3-5 mm lengths; S15. The cut carbon fiber is placed in concentrated nitric acid for surface oxidation treatment; S16. The treated carbon fiber is rinsed with deionized water until neutral, and then dried in a vacuum drying oven at 80-100 ° C for 6-8 hours to obtain a carbon fiber filler; S17. Adding 2-4 parts by mass of graphene to N-methylpyrrolidone, stirring at a stirring speed of 1000-1500 r / min for 30-60 minutes, the graphene is initially dispersed in N-methylpyrrolidone to obtain a preliminary graphene solution; S18. Then, the graphene preliminary solution is subjected to ultrasonic treatment with an ultrasonic power of 200-300 W and an ultrasonic time of 30-60 minutes to further improve the dispersion uniformity of the graphene and obtain a graphene filler.

7. The method for preparing a heat dissipation material according to claim 6, characterized in that: The dispersant is sodium dodecylbenzene sulfonate; And / or the ultrasonic power of the ultrasonic treatment is set to 300-500W, and the ultrasonic time is 1-2 hours; And / or the mass ratio of the concentrated nitric acid to the carbon fiber is 5:1-10:1, the treatment time is 2-4 hours, and the temperature is controlled at 60-80°C.

8. The method for preparing a heat dissipation material according to claim 5, characterized in that: In step S2, the phenolic resin matrix is ​​heated and stirred, and the specific steps of adding the filler formed by pretreatment into the phenolic resin during the stirring process are as follows: S21. The mass fraction of 40-50 phenolic resin is heated to 60-80 ° C, and the heating process is continuously stirred; S22. The pretreated carbon nanotube dispersion, carbon fiber and graphene dispersion are slowly added to the heated phenolic resin in sequence while stirring with a mechanical stirrer; S23. The stirring speed is 500-800 r / min and the stirring time is 40-60 minutes to evenly distribute the filler in the phenolic resin matrix.

9. The method for preparing a heat dissipation material according to claim 5, characterized in that: In step S4, the specific steps of placing the mold containing the material into an oven for curing are as follows: Perform low-temperature pre-curing, set the curing temperature to 80-100°C and the time to 1-2 hours; Perform medium temperature curing, set the temperature to 120-140℃, and last for 2-3 hours; Perform high temperature curing, set the temperature to 160-180℃, and the time is 1-2 hours.

10. The method for preparing a heat dissipation material according to claim 5, characterized in that: In step S3, the specific steps of slowly adding the curing agent to the mixed resin and filler system while stirring are as follows: S31. Set the required curing agent mass M g and the total mass of phenolic resin and filler M t ; S32. Introduce a machine learning model to predict the optimal curing agent addition rate R based on historical data pred , where R pred The expression is as follows: R pred =f(M t ,T initial ,η initial ,C) Among them, R pred is the predicted curing agent addition rate, M t is the total mass, T initial is the initial temperature, η initial is the initial viscosity, C is the mass of the curing agent, and the function f uses multiple inputs to train the model; S33. Set the target mixture temperature T target and target viscosity η target , and calculate the corresponding curing agent addition rate: Wherein, Mg is the total mass of the curing agent, and T is the set addition time; S34. Dynamically adjust the curing agent addition rate, wherein the addition rate is expressed as follows: R adjusted =R pred +k f ·(T target -T m )+k v ·(or target -η(t)) Among them, R adjusted is the adjusted rate, K f is the adjustment coefficient of the temperature feedback effect, K v is the adjustment factor for the feedback effect of viscosity, Tm is the current temperature of the mixture, and η(t) is the change in the viscosity of the mixture with time; S35. Set stirring speed V s , dynamically adjusted according to real-time viscosity and temperature changes: Among them, V s is the stirring speed, V mix is the volume of the mixture, k is the proportionality constant, k s is the adjustment factor related to temperature change, K v is the adjustment factor related to the viscosity change; S36. Use optimization algorithms to adjust flow and stirring speed to achieve multivariable optimization: Among them, J is the objective function, Xi represents different control parameters, Xtarget represents the target value corresponding to the control parameter, ω i is the weight; S37. When the preset total mass of curing agent M is reached g When the curing agent is added, the stirring speed is set at 800-1200r / min and the stirring is maintained for 10 minutes to ensure uniform mixing; S38. Strictly control the system temperature through the heating device and maintain it at 25-30℃ to avoid premature reaction of the curing agent due to temperature fluctuations.

Citation Information

Patent Citations

  • Graphene modified carbon fiber resin material

    CN105086361A

  • Thermosetting resin composition based on graphene three-dimensional heat conduction network chain, and preparation method thereof

    CN111303586A